The Effectiveness of Autogenic Relaxation on Emotion Regulation In Boxing Athletes In Koni Makassar City - Pasenrigading, Andi Riola; Ridfah, Ahmad; Ismail, Ismalandari (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
One method that boxing athletes can use to improve emotional regulation is the autogenic relaxation technique. This study aimed to determine the effectiveness of autogenic relaxation on the emotional regulation of boxing athletes. The study participants were five boxing athletes, one female who obtained an emotion regulation score in the medium category at the time of pretest posttest administration and four male sex who obtained an emotion regulation score in the high category at the time of pretest posttest administration. The method used in this study is an experimental method with a time series design experiment design. The instrument used in this study is an emotion regulation scale compiled by researchers based on aspects from Gross (2003). The results of quantitative analysis using visual inspection charts showed an increase in the emotional regulation score of boxing athletes before and after autogenic relaxation training. All five study participants obtained emotion regulation scores in the medium and high categories. Qualitative analysis is carried out by analyzing the results of evaluation sheets as research support. The implication of this study is that autogenic relaxation exercises carried out repeatedly can improve the ability of emotional regulation in boxing athletes at KONI Makassar City.